Bachelor's Degree Final Project in Business Administration: From theory to experience at the Business and Tourism Faculty, Ourense campus, (University of Vigo). - Patricio Sanchez Fernandez (Universitat Politècnica de València, 2013)
The new educational scenario promoted by the European Higher Education Area (EHEA) has brought significant changes in the day-to-day teaching of undergraduate degrees. Among these changes we can mention the appearance of a Final Project as a compulsory subject in all degrees, including the degree in Business Administration. This paper examines the experience in this regard of the Faculty of Business Administration and Tourism of the University of Vigo. This Faculty located in the Ourense Campus already has two years of experience as regards teaching and academic organization of the Final Project since its establishment in the academic year 2010-11. For this purpose the paper begins by reviewing the main characteristics of the Final Project. This review is made in the Spanish context of the new degrees adapted to the EHEA and paying special attention to the degree in Business Administration. Then we present the particular case of this Faculty where you can identify the main pillars on which its implementation was based as well as the future challenges that those responsible for the Faculty still face.